5,11,17,23-Tetrakis(chloromethyl)-25,26,27,28-tetrapropoxycalix[4]arene - Kutter, Felix (International Union of Crystallography, 2011)
The title calix[4]arene, C(44)H(52)Cl(4)O(4), displays the 1,3-alternate conformation with crystallographically imposed twofold symmetry. Four phenolic rings of the calixarene backbone are tilted into the calix cavity, making dihedral angles of 77.42 (2) and 77.71 (2)° with the plane of the four bridging methylene C atoms. Pairs of opposite aromatic rings make dihedral angles of 25.16 (3) and 24.58 (4)° with each other. In the crystal, the calixarene molecules pack with the formation of infinite columns along the b axis. The crystal packing shows a network of C—H⋯Cl contacts, which can be considered as non-classical hydrogen bonds.